Management of Psychosis in Perinatal Period in Local Psychiatric Inpatient Unit, Current Pathways and Proposal to Improve Standards of Care - Irum Bibi; Oleksandr Khrypunov; Nimisha Agarwal; Kazi Rahman (BJPsych Open)
Aims: To enhance the quality of care for patients experiencing psychotic episodes during the perinatal period (antenatal and postnatal) by improving service pathways and management.